The effect of algal blooms on fish in their inshore nursery grounds in the Gulf of Gdańsk. (12th September 2017) - Pawelec, Anna J.; Sapota, Mariusz R.; Kobos, Justyna
Abstract : Studies of cyanobacterial bloom dynamics show that the highest biomass accumulation of Nodularia spumigena is observed in the shallowest area of the Gulf of Gdańsk in summer. In the same region and time, the highest fish abundance is observed. Mostly young individuals of gobies, small sandeel, flounder, three-spine stickleback and young herring occur. In this work we compare how toxic blooms of cyanobacteria influence the number and structure of fish communities in a coastal zone. The results obtained in our study were rather unexpected. More fish species were caught and the biomass of fish was higher during a bloom than in a month following the sampling (no bloom).